Near-zero-expansion C / Si3N4-SiC composite material as well as preparation method and application thereof

The C/Si3N4-SiC composite material addresses the long preparation cycles and complexity of existing carbon fiber composites by using a chemical vapor infiltration process to achieve near-zero thermal expansion and maintain mechanical integrity, suitable for space optical mechanical structures.

CN119191852AActive Publication Date: 2024-12-27NORTHWESTERN POLYTECHNICAL UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411340906.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Existing carbon fiber reinforced multi-layer matrix composite materials for space optical mechanical structures have long preparation cycles and complex processes, making them unsuitable for large-scale production, despite achieving a thermal expansion coefficient of 0.12×10^-6 K^-1.

Method used

A near-zero expansion C/Si3N4-SiC composite material is prepared using a chemical vapor infiltration process, where the deposition time of the silicon nitride matrix is adjusted to completely wrap the carbon fiber bundle, forming diffusely distributed microcracks and a silicon carbide matrix to constrain the fibers, reducing the thermal expansion coefficient to less than 0.1×10^-6 K^-1.

Benefits of technology

The process significantly reduces the preparation cycle to 2-3 months, achieves near-zero thermal expansion, and maintains excellent mechanical properties, with an average thermal expansion coefficient of 0.03×10^-6 K^-1 to 0.07×10^-6 K^-1, suitable for space optical mechanical structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191852A_ABST
    Figure CN119191852A_ABST
Patent Text Reader

Abstract

The invention discloses a near-zero-expansion C / Si3N4-SiC composite material as well as a preparation method and application thereof, and relates to the technical field of ceramic-based composite materials. The composite material comprises a carbon fiber reinforced silicon nitride-based porous composite material and a silicon carbide matrix coated on the surface of the carbon fiber reinforced silicon nitride-based porous composite material, the carbon fiber reinforced silicon nitride-based porous composite material comprises a carbon fiber preform formed by weaving carbon fiber bundles, a pyrolytic carbon interface layer is deposited on a carbon fiber bundle in the carbon fiber preform, and the pyrolytic carbon interface layer is also coated with a silicon nitride matrix. According to the method, the deposition time of the silicon nitride substrate is regulated and controlled, so that the silicon nitride substrate completely wraps the carbon fiber bundle, dispersively distributed microcracks are formed in the fiber bundle, and near-zero expansion is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic-based composite materials, and in particular to a near-zero expansion C / Si3N4-SiC composite material and a preparation method and application thereof. Background Art

[0002] With the continuous development of science and technology, countries have also continuously invested manpower and material resources to develop scientific exploration satellites. Space exploration satellites are mainly composed of optical components and the space optical mechanical structures that carry them. To achieve ultra-high detection accuracy, the space optical mechanical structures must have high structural stability and thermal stability, that is, the absolute value of the expansion coefficient of the material within the service temperature range must reach 10 -7 K -1 Level or even lower. At the same time, facing the vibration of rocket launch, the materials used are required to have excellent mechanical properties. In order to reduce the launch cost of space exploration satellites, the materials used in space optomechanical structural parts are required to have low density. Faced with the complex space environment, the materials are required to have properties such as resistance to space radiation and anti-antibody impact. Therefore, the materials used in space optomechanical structural parts need to have a near-zero expansion coefficient, excellent mechanical properties, low density and good environmental stability.

[0003] Carbon fiber reinforced ceramic matrix composites have the advantages of low density, excellent mechanical properties, low expansion coefficient and good environmental stability, making them an ideal choice for the new generation of space optical and mechanical materials. The prior art discloses a near-zero expansion carbon fiber reinforced multi-layer matrix composite material, which greatly reduces the expansion coefficient of the current ceramic matrix composite material by mainly regulating the number of cycles and layer thickness ratio of the multi-layer matrix. The average thermal expansion coefficient of the prepared composite material is 0.12×10 -6 K -1 , reaching an advanced level. However, when introducing a low expansion phase into C / SiC, the carbon fiber reinforced multi-layer composite material requires the use of alternating deposition of silicon carbide and silicon nitride, and the deposition requires at least 9 furnaces or more, resulting in a material preparation cycle of 4-5 months, and the complex process is not conducive to large-scale production. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problems of long preparation cycle and complex preparation process of carbon fiber reinforced multi-layer matrix composite materials. The present invention provides a near-zero expansion C / Si3N4-SiC composite material and its preparation method and application. The method adopts a chemical vapor infiltration process, and by adjusting the deposition time of the silicon nitride matrix, the Si3N4 matrix completely wraps the carbon fiber bundle, and utilizes the amorphous characteristics of silicon nitride to form a large number of diffusely distributed microcracks in the fiber bundle. The outer layer of silicon carbide has a high degree of crystallization, which constrains the internal fibers and the silicon nitride matrix, thereby achieving near-zero expansion.

[0005] The first object of the present invention is to provide a near-zero expansion C / Si3N4-SiC composite material, characterized in that the composite material comprises a carbon fiber reinforced silicon nitride-based porous composite material, and a silicon carbide matrix coated on the surface of the carbon fiber reinforced silicon nitride-based porous composite material; The carbon fiber reinforced silicon nitride-based porous composite material comprises a carbon fiber preform woven from carbon fiber bundles; a pyrolytic carbon interface layer is deposited on the carbon fiber bundles in the carbon fiber preform, and the pyrolytic carbon interface layer is also coated with a silicon nitride matrix; The fiber monofilaments inside the carbon fiber bundle contain a silicon nitride matrix; the fiber monofilaments at the edge of the carbon fiber bundle and the silicon carbide matrix contain a silicon nitride matrix with a thickness of 0.5 to 5 μm.

[0006] Preferably, the thickness of the pyrolytic carbon interface layer is 100-500 nm; the thickness of the silicon carbide matrix layer outside the carbon fiber bundle is 0.02-0.3 mm.

[0007] Preferably, the diameter of the fiber monofilaments in the carbon fiber bundle is 4-8 μm; the number of the fiber monofilaments in the carbon fiber bundle is 1K, 3K, 6K or 12K; the carbon fibers in the carbon fiber bundle are T series fibers; The carbon fiber preform structure includes a 2D carbon fiber preform, a 2.5D carbon fiber preform or a 3D woven carbon fiber preform.

[0008] Preferably, the density of the composite material is 1.9-2.1 g / cm 3 The open porosity is 8~15vol.%; the absolute value of the thermal expansion coefficient of the composite material in the temperature range of -100~100℃ is less than 0.1×10 -6 K -1 .

[0009] The second object of the present invention is to provide a method for preparing a near-zero expansion C / Si3N4-SiC composite material, comprising the following steps: Weaving continuous carbon fiber bundles into carbon fiber preforms with different structures and a fiber volume fraction of ≥38%; The carbon fiber preform is placed in a vacuum furnace, the pressure is set to <300Pa, the temperature is 800-900°C, argon and propylene are introduced, and the temperature is kept for 45-200 hours, a pyrolytic carbon interface layer is deposited on the surface of the carbon fiber preform, and then a heat treatment is performed at 1200-1900°C for 1-2 hours; The carbon fiber preform after the pyrolytic carbon interface layer is deposited and heat treated is set to a pressure of less than 300 Pa and a temperature of 800-1100°C, and argon, hydrogen, silicon tetrachloride and ammonia are introduced, and the carbon fiber bundle is completely wrapped by the silicon nitride matrix by adjusting the deposition time to obtain a carbon fiber reinforced silicon nitride-based porous composite material; A carbon fiber reinforced silicon nitride-based porous composite material is placed in a deposition furnace, the pressure is set to <300Pa, the temperature is 1000~1100℃, argon, hydrogen and trichloromethylsilane are introduced, a silicon carbide matrix is ​​generated by reaction on the surface of the silicon nitride matrix, and the pores between the carbon fiber bundles are filled to obtain a near-zero expansion C / Si3N4-SiC composite material.

[0010] Preferably, when the pyrolytic carbon interface layer is deposited on the surface of the carbon fiber preform, the flow rate of the introduced argon gas is 2-4 L / min, and the flow rate of the introduced propylene gas is 2-4 L / min.

[0011] Preferably, when preparing the porous C / Si3N4 composite material, the flow rate of argon is 2~4L / min, the flow rate of hydrogen is 7~9L / min, the flow rate of silicon tetrachloride is 3~5L / min, and the flow rate of ammonia is 2~4L / min.

[0012] Preferably, when a silicon carbide substrate is generated by reaction on the surface of a silicon nitride substrate, the flow rate of the introduced argon gas is 2-4 L / min; the flow rate of the introduced hydrogen gas is 4-6 L / min; and the molar mass ratio of the hydrogen gas to trichloromethylsilane is 10:1.

[0013] The third object of the present invention is to provide a near-zero expansion C / Si3N4-SiC composite material for use in space optical mechanical structures.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a near-zero expansion C / Si3N4-SiC composite material and a preparation method and application thereof. The present invention adjusts the deposition time of the silicon nitride matrix so that the fiber bundle is completely wrapped. The prepared near-zero expansion C / Si3N4-SiC composite material has an average thermal expansion coefficient of 0.03×10 -6 K -1 The absolute value of its expansion coefficient is less than 0.1×10 -6 K -1 , achieving the goal of near-zero inflation; The expansion performance of the carbon fiber ceramic matrix composite material provided by the present invention depends not only on the expansion coefficient of each component, but also on the interaction between the fiber and the matrix. In traditional carbon fiber reinforced ceramic matrix composite materials, the matrix and the fiber in the bundle are strongly combined, so that the negative expansion performance of the fiber cannot be well exerted, and the cracks generated are mostly transverse cracks between the fiber bundles, which cannot well alleviate the thermal mismatch between the fiber and the matrix. After research, it was found that the matrix in the fiber bundle greatly affects the expansion performance of the composite material.

[0015] The present invention adopts a chemical vapor infiltration process, and by adjusting the deposition time of the silicon nitride matrix, the silicon nitride matrix completely wraps the carbon fiber bundle to prepare a C / Si3N4-SiC composite material, and the generated cracks are controlled inside the fiber bundle, so as to better alleviate the thermal mismatch between the fiber and the matrix, greatly reduce the expansion coefficient of the carbon fiber reinforced ceramic matrix composite material, and distribute the silicon carbide matrix with better modulus between the fiber bundles, thereby ensuring better mechanical properties while reducing the expansion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The scanning electron microscope image and EDS of the C / Si3N4-SiC composite material prepared in Example 1.

[0017] Figure 2 Schematic diagram of the expansion performance of the C / Si3N4-SiC composite material prepared in Example 1 in the temperature range of -80~50°C, where a is the linear expansion curve and b is the curve of the expansion coefficient changing with temperature.

[0018] Figure 3 ] are the mechanical property curves of the C / Si3N4-SiC composite material prepared in Example 1, where a is the bending stress-strain curve and b is the fracture toughness force-displacement curve.

[0019] Figure 4 Schematic diagram of the expansion performance of the C / SiC composite material prepared in Control Example 1 within the temperature range of -80 to 50°C, wherein a is the linear expansion curve and b is the curve of the expansion coefficient varying with temperature.

[0020] Figure 5 The mechanical property curves of the C / SiC composite material prepared in Control Example 1, wherein a is the bending stress-strain curve, and b is the fracture toughness force-displacement curve. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0022] The first aspect of the present invention provides a near-zero expansion C / Si3N4-SiC composite material, the composite material comprising a carbon fiber reinforced silicon nitride-based porous composite material, and a silicon carbide matrix coated on the surface of the carbon fiber reinforced silicon nitride-based porous composite material; The carbon fiber reinforced silicon nitride-based porous composite material comprises a carbon fiber preform woven from carbon fiber bundles; a pyrolytic carbon interface layer is deposited on the carbon fiber bundles in the carbon fiber preform, and the pyrolytic carbon interface layer is also coated with a silicon nitride matrix; The fiber monofilaments inside the carbon fiber bundle contain a silicon nitride matrix; the fiber monofilaments at the edge of the carbon fiber bundle and the silicon carbide matrix contain a silicon nitride matrix with a thickness of 0.5 to 5 μm.

[0023] The thickness of the pyrolytic carbon interface layer is 100-500 nm; the thickness of the silicon carbide matrix layer outside the carbon fiber bundle is 0.02-0.3 mm.

[0024] The diameter of the fiber monofilaments in the carbon fiber bundle is 4-8 μm; the number of the fiber monofilaments in the carbon fiber bundle is 1K, 3K, 6K or 12K; the carbon fibers in the carbon fiber bundle are T series fibers; The carbon fiber preform structure includes a 2D carbon fiber preform, a 2.5D carbon fiber preform or a 3D woven carbon fiber preform.

[0025] The density of the composite material is 1.9-2.1 g / cm 3 The open porosity is 8~15vol.%; the absolute value of the thermal expansion coefficient of the composite material in the temperature range of -100~100℃ is less than 0.1×10 -6 K -1 .

[0026] In one embodiment, a near-zero expansion C / Si3N4-SiC composite material includes a carbon fiber bundle, a pyrolytic carbon interface layer on the surface of the carbon fiber bundle, a silicon nitride matrix layer that completely wraps the carbon fiber bundle, and a silicon carbide matrix layer outside the carbon fiber bundle.

[0027] The carbon fiber adopts T series fiber: T300, T700 and T800, etc. The silicon nitride matrix layer completely wrapping the carbon fiber bundle is: only silicon nitride matrix exists between the fiber monofilaments inside the carbon fiber bundle, and silicon nitride matrix with a thickness of 0.5-5 μm exists between the fiber monofilaments at the edge of the carbon fiber bundle and the silicon carbide matrix; The thickness of the silicon carbide matrix layer outside the carbon fiber bundle is 0.02~0.3mm.

[0028] Preferably, the absolute value of the thermal expansion coefficient of the near-zero expansion C / Si3N4-SiC composite material in the temperature range of -80 to 50°C is less than 0.1×10 -6 K -1 .

[0029] A second aspect of the present invention provides a method for preparing a near-zero expansion C / Si3N4-SiC composite material, comprising the following steps: Weaving continuous carbon fiber bundles into carbon fiber preforms with different structures and a fiber volume fraction of ≥38%; The carbon fiber preform is placed in a vacuum furnace, the pressure is set to <300Pa, the temperature is 800-900°C, argon and propylene are introduced, and the temperature is kept for 45-200 hours to deposit a pyrolytic carbon interface layer on the surface of the carbon fiber preform; then a heat treatment is performed at 1200-1900°C for 1-2 hours; The carbon fiber preform after the pyrolytic carbon interface layer is deposited and heat treated is set at a pressure of less than 300 Pa and a temperature of 800-1100°C, and argon, hydrogen, silicon tetrachloride and ammonia are introduced. The carbon fiber bundle is completely wrapped by the silicon nitride matrix by adjusting the deposition time to obtain a carbon fiber reinforced silicon nitride-based porous composite material (porous C / Si3N4 composite material); The C / Si3N4 composite material is placed in a deposition furnace, the pressure is set to <300Pa, the temperature is 1000~1100℃, argon, hydrogen and trichloromethylsilane are introduced, a silicon carbide matrix is ​​generated by reaction on the surface of the silicon nitride matrix, and the pores between the carbon fiber bundles are filled to obtain a near-zero expansion C / Si3N4-SiC composite material.

[0030] When depositing the pyrolytic carbon interface layer on the surface of the carbon fiber preform, the flow rate of the argon gas is 2-4 L / min, and the flow rate of the propylene gas is 2-4 L / min; preferably, the flow rate of the argon gas is 3 L / min, and the flow rate of the propylene gas is 3 L / min.

[0031] When preparing porous C / Si3N4 composite materials, the flow rate of argon gas is 2~4L / min, the flow rate of hydrogen gas is 7~9L / min, the flow rate of silicon tetrachloride is 3~5L / min, and the flow rate of ammonia gas is 2~4L / min; preferably, the flow rate of argon gas is 3L / min, the flow rate of hydrogen gas is 8L / min, the flow rate of silicon tetrachloride is 4L / min, and the flow rate of ammonia gas is 3L / min.

[0032] When a silicon carbide substrate is generated by reaction on the surface of a silicon nitride substrate, the flow rate of the argon gas is 2 to 4 L / min; the flow rate of the hydrogen gas is 4 to 6 L / min, preferably, the flow rate of the argon gas is 3 L / min, and the flow rate of the hydrogen gas is 5 L / min; the molar mass ratio of the hydrogen gas to trichloromethylsilane is 10:1.

[0033] In one embodiment, a method for preparing a near-zero expansion C / Si3N4-SiC composite material comprises the following steps: Step 1: stacking plain carbon fiber cloth woven from continuous carbon fiber bundles, and then stitching the continuous carbon fiber bundles along the thickness direction to obtain a carbon fiber preform with a fiber volume fraction of ≥38%; Step 2: placing the carbon fiber preform prepared in step 1 in a vacuum furnace with a pressure of less than 300 Pa and a temperature of 800-900° C., introducing argon as a diluent gas, introducing propylene as a carbon source, and keeping the temperature for 45-200 hours, and depositing a pyrolytic carbon interface layer with a thickness of 100-500 nm on the surface of the carbon fiber; Step 3: placing the carbon fiber preform on which the pyrolytic carbon interface layer is deposited in step 2 in an environment with a pressure of less than 300 Pa for a high temperature heat treatment at 1200-1900° C. for 1-2 hours; Step 4: placing the heat-treated carbon fiber preform prepared in step 3 in a deposition furnace, evacuating to a pressure of less than 300 Pa and heating to 800-1100°C, then introducing argon as a carrier gas, hydrogen as a diluent gas, silicon tetrachloride as a silicon source, and ammonia as a nitrogen source, and adjusting the deposition time so that the carbon fiber bundle is completely wrapped by the silicon nitride matrix to obtain a C / Si3N4 porous composite material; Step 5: Place the C / Si3N4 composite material prepared in step 4 in a deposition furnace, evacuate to a pressure of <300 Pa and heat to 1000-1100°C, then introduce argon as a carrier gas, hydrogen as a diluent gas, and trichloromethylsilane as a carbon source to generate a silicon carbide matrix on the surface of the silicon nitride matrix through reaction, fill the pores between the carbon fiber bundles in the composite material, and obtain a density of 1.9-2.1 g / cm 3 and near-zero expansion C / Si3N4-SiC composites with an open porosity of 8~15vol.%.

[0034] The number of fiber filaments in the continuous carbon fiber bundle in step 1 includes but is not limited to 1K, 3K, 6K or 12K. When the number of fiber filaments in the continuous carbon fiber bundle is 1K, 3K, 6K or 12K, the fiber bundle filaments are completely wrapped by adjusting the deposition time of the silicon nitride matrix.

[0035] As described in step 1, the plain carbon fiber cloth woven with continuous carbon fiber bundles is stacked, and then the continuous carbon fiber bundles are sewn along the thickness direction to obtain 2D plying, 2.5D weaving and 3D weaving molding structures.

[0036] The carbon fiber preform structure includes but is not limited to a 2D carbon fiber preform, a 2.5D carbon fiber preform, and a 3D woven carbon fiber preform.

[0037] Among them, the 2D carbon fiber preform is made by weaving continuous carbon fiber bundles into plain carbon fiber cloth, then cutting the fiber cloth into a certain size and stacking it, and then clamping it with a mold and sewing and shaping it along the stacking direction of the carbon fiber cloth with the carbon fiber bundle to finally obtain a 2D carbon fiber preform.

[0038] 2.5D carbon fiber preforms and 3D woven carbon fiber preforms are woven by machines.

[0039] When the carbon fiber preform is a 2D carbon fiber preform, a 2.5D carbon fiber preform, or a 3D three-dimensional braided carbon fiber preform, the fiber bundles are completely wrapped by adjusting the deposition time of the silicon nitride matrix.

[0040] A third aspect of the present invention provides an application of a near-zero expansion C / Si3N4-SiC composite material in a space optical-mechanical structural component.

[0041] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0042] Example 1 This embodiment uses T300 carbon fiber with a fiber tow size of 1K to prepare a near-zero expansion C / Si3N4-SiC composite material, which specifically includes the following steps: (1) Preparation of carbon fiber preform: A T300 carbon fiber bundle with a fiber monofilament quantity of 1K was woven into a plain fiber cloth, which was then cut into a size of: length × width = 170 mm × 110 mm, 20 layers were stacked, and then 1K T300 continuous carbon fiber bundles were sewn along the thickness direction of the stacking, and finally fixed with a graphite fixture to obtain a 2D carbon fiber preform; (2) Preparation of pyrolytic carbon interface layer: The 2D carbon fiber preform prepared in step (1) was placed in a deposition furnace at a pressure of 5 KPa and a temperature of 900°C, and argon gas was introduced at a flow rate of 3 L / min and propylene was introduced at a flow rate of 3 L / min. The deposition time was 3 h, and a 200 nm pyrolytic carbon interface layer was obtained on the surface of the fiber bundle, which was then heat treated at 1800°C for 2 h.

[0043] (3) Preparation of the matrix: The carbon fiber preform after heat treatment prepared in step (2) was placed in a deposition furnace, evacuated to a pressure of 5 KPa and heated to 850°C, and then introduced argon at a flow rate of 3 L / min, hydrogen at a flow rate of 8 L / min, silicon tetrachloride at a flow rate of 4 L / min, and ammonia at a flow rate of 3 L / min. The deposition time was 80 h to prepare a C / Si3N4 porous composite material. The porous C / Si3N4 composite was then The composite material was placed in a deposition furnace, evacuated to a pressure of 5 KPa and heated to 1100 ° C, and then introduced argon at a flow rate of 3 L / min, hydrogen at a flow rate of 5 L / min, and trichloromethylsilane, the molar mass ratio of trichloromethylsilane to hydrogen was 1:10, and the deposition time was 320 h. A silicon carbide matrix was generated by reaction on the surface of the silicon nitride matrix, and the pores between the fiber bundles in the composite material were filled to obtain a density of 2.06 ± 0.80 g / cm 3 , C / Si3N4-SiC composite material with open porosity of 9±1%.

[0044] It should be noted that the average thermal expansion coefficient of the C / Si3N4-SiC composite material prepared in Example 1 within the temperature range of -80 to 50°C is 0.03×10 -6 K -1 The absolute value of the thermal expansion coefficient of the composite material is less than 0.1×10 -6 K -1 , achieving the goal of near-zero inflation.

[0045] Example 2 This embodiment uses T700 carbon fiber with a fiber tow size of 3K to prepare a near-zero expansion C / Si3N4-SiC composite material, which specifically includes the following steps: (1) Preparation of fiber preform: A T700 carbon fiber bundle with a fiber monofilament quantity of 3K was woven into a plain fiber cloth, which was then cut into length × width = 150 mm × 100 mm, laminated with 16 layers, and then sewn along the thickness direction of the laminate with a 1K T300 continuous carbon fiber bundle, and finally fixed with a graphite fixture to obtain a 2D carbon fiber preform; (2) Interface preparation: The 2D carbon fiber preform prepared in step (1) was placed in a deposition furnace at a pressure of 5 KPa and a temperature of 900°C, and argon gas was introduced at a flow rate of 3 L / min and propylene was introduced at a flow rate of 3 L / min. The deposition time was 3 h, and a 200 nm pyrolytic carbon interface layer was obtained on the surface of the fiber bundle, which was then heat treated at 1900°C for 1 h.

[0046] (3) Si3N4 matrix layer deposition: the carbon fiber preform prepared in step (2) is placed in a deposition furnace, evacuated to a pressure of 5 KPa and heated to 850°C, and then argon gas at a flow rate of 3 L / min, hydrogen gas at a flow rate of 8 L / min, silicon tetrachloride at a flow rate of 4 L / min, and ammonia gas at a flow rate of 3 L / min are introduced, and the deposition time is 120 h to prepare a C / Si3N4 porous composite material; (4) Deposition of SiC matrix layer: The porous C / Si3N4 composite material prepared in step (3) was placed in a deposition furnace, evacuated to a pressure of 5 KPa and heated to 1100°C, and then introduced argon at a flow rate of 3 L / min, hydrogen at a flow rate of 5 L / min, and trichloromethylsilane, wherein the molar mass ratio of trichloromethylsilane to hydrogen was 1:10. The deposition time was 280 h, and a silicon carbide matrix was generated on the surface of the silicon nitride matrix by reaction, filling the pores between the fiber bundles in the composite material to obtain a density of 2.01±0.42 g / cm 3 , C / Si3N4-SiC composite material with open porosity of 10±1%.

[0047] It should be noted that the average thermal expansion coefficient of the C / Si3N4-SiC composite material prepared according to Example 2 in the temperature range of -80 to 50°C is 0.07×10 -6 K -1 The absolute value of the thermal expansion coefficient of the composite material is less than 0.1×10 -6 K -1 , achieving the goal of near-zero inflation.

[0048] Example 3 This embodiment uses a 3D4d carbon fiber preform to prepare a near-zero expansion C / Si3N4-SiC composite material, which specifically includes the following steps: (1) Preparation of fiber preform: T300 carbon fiber bundles with a fiber filament count of 1K are interwoven in space by a machine to form a three-dimensional four-directional (3D4d) carbon fiber preform with the dimensions of: length × width × height = 100 mm × 100 mm × 5 mm.

[0049] (2) Preparation of pyrolytic carbon interface layer: The 3D4d carbon fiber preform prepared in step (1) was placed in a deposition furnace at a pressure of 5 KPa and a temperature of 900°C, and argon gas was introduced at a flow rate of 3 L / min and propylene was introduced at a flow rate of 3 L / min. The deposition time was 1.5 h, and a 100 nm pyrolytic carbon interface layer was obtained on the surface of the fiber bundle, which was then heat treated at 1800°C for 2 h.

[0050] (3) Preparation of the matrix: The carbon fiber preform after heat treatment prepared in step (2) was placed in a deposition furnace, evacuated to a pressure of 5 KPa and heated to 800 °C, and then introduced argon at a flow rate of 3 L / min, hydrogen at a flow rate of 8 L / min, silicon tetrachloride at a flow rate of 4 L / min, and ammonia at a flow rate of 3 L / min. The deposition time was 160 h to prepare a C / Si3N4 porous composite material. The porous C / Si3N4 composite was then The composite material was placed in a deposition furnace, evacuated to a pressure of 5 KPa and heated to 1100 ° C, and then introduced argon at a flow rate of 3 L / min, hydrogen at a flow rate of 5 L / min, and trichloromethylsilane, the molar mass ratio of trichloromethylsilane to hydrogen was 1:10, and the deposition time was 300 h. The silicon carbide matrix was generated by reaction on the surface of the silicon nitride matrix, and the pores between the fiber bundles in the composite material were filled to obtain a density of 2.10 ± 0.80 g / cm 3 , C / Si3N4-SiC composite material with open porosity of 9±1%.

[0051] It should be noted that the average thermal expansion coefficient of the C / Si3N4-SiC composite material prepared according to Example 3 in the temperature range of -80 to 50°C is 0.02×10 -6 K -1 The absolute value of the thermal expansion coefficient of the composite material is less than 0.1×10 -6 K -1 , achieving the goal of near-zero inflation.

[0052] Comparative Example 1 This comparative example uses T300 carbon fiber with a fiber tow size of 1K to prepare a near-zero expansion C / SiC composite material, which specifically includes the following steps: (1) Preparation of carbon fiber preform: A T300 carbon fiber bundle with a fiber monofilament quantity of 1K was woven into a plain fiber cloth, which was then cut into a size of 170 mm × 110 mm, stacked with 20 layers, and then sewn along the thickness direction of the stack with a 1K T300 continuous carbon fiber bundle, and finally fixed with a graphite fixture to obtain a 2D carbon fiber preform; (2) Preparation of pyrolytic carbon interface layer: The 2D carbon fiber preform prepared in step (1) was placed in a deposition furnace at a pressure of 5 KPa and a temperature of 900°C, and argon gas was introduced at a flow rate of 3 L / min and propylene was introduced at a flow rate of 3 L / min. The deposition time was 3 h, and a 200 nm pyrolytic carbon interface layer was obtained on the surface of the fiber bundle, which was then heat treated at 1800°C for 2 h.

[0053] (3) Preparation of the matrix: The carbon fiber preform prepared in step (2) after heat treatment is placed in a deposition furnace, evacuated to a pressure of 5 KPa and heated to 1100°C, and then introduced argon at a flow rate of 3 L / min, hydrogen at a flow rate of 5 L / min, and trichloromethylsilane, wherein the molar mass ratio of trichloromethylsilane to hydrogen is 1:10. The deposition time is 400 h, and the surface of the fiber bundle is reacted to generate a silicon carbide matrix, and a density of 2.12±0.50 g / cm 3 , C / Si3N4-SiC composite material with open porosity of 10±1%.

[0054] It should be noted that the average thermal expansion coefficient of the C / SiC composite material prepared according to Comparative Example 1 in the temperature range of -80 to 50 °C is 0.93×10 -6 K -1 Compared with the control example 1, after 80h of deposition of silicon nitride in the fiber bundle, the expansion coefficient of Example 1 was reduced to 0.03×10 -6 K -1 , that is, near-zero expansion is achieved.

[0055] In order to illustrate the relevant properties of the C / Si3N4-SiC composite material provided by the present invention, it is described in conjunction with the accompanying drawings.

[0056] Figure 1 The scanning electron microscope image and EDS of the C / Si3N4-SiC composite material prepared in Example 1.

[0057] from Figure 1 It can be seen from the SEM image that the material is composed of carbon fiber bundles, silicon nitride matrix and silicon carbide matrix, and there are a lot of cracks in the matrix within the fiber bundle; Figure 1 It can be seen from the EDS analysis that the nitrogen element wraps the carbon element, indicating that the silicon nitride matrix completely wraps the carbon fiber bundle, and there is a certain thickness of silicon nitride matrix between the fiber filaments outside the fiber bundle and the silicon carbide matrix.

[0058] Figure 2 Schematic diagram of the expansion performance of the C / Si3N4-SiC composite material prepared in Example 1 in the temperature range of -80~50°C, where a is the linear expansion curve and b is the curve of the expansion coefficient changing with temperature.

[0059] from Figure 2 It can be seen from a that the linear expansion of the composite material first decreases and then increases, and the trend is gentle. Figure 2 As can be seen in b, the expansion coefficient of the material is low. The average thermal expansion coefficient in the temperature range of -80~50℃ is 0.03×10 -6 K -1The absolute value of the thermal expansion coefficient of the composite material is less than 0.1×10 -6 K -1 , achieving the goal of near-zero inflation.

[0060] Figure 3 ] are the mechanical property curves of the C / Si3N4-SiC composite material prepared in Example 1, where a is the bending stress-strain curve and b is the fracture toughness force-displacement curve.

[0061] After testing, the bending strength of the C / Si3N4-SiC composite material prepared in Example 1 is 329±5MPa, and the fracture toughness is 22.3±1.4MPa / m 2 .

[0062] Figure 4 Schematic diagram of the expansion performance of the C / SiC composite material prepared in Control Example 1 within the temperature range of -80 to 50°C, wherein a is the linear expansion curve and b is the curve of the expansion coefficient varying with temperature.

[0063] from Figure 4 It can be seen from a that the linear expansion of the C / SiC composite material gradually increases with the increase of temperature. Figure 4 As can be seen from b, the engineering expansion coefficient of the material also gradually increases with the increase of temperature. The average thermal expansion coefficient in the temperature range of -80~50℃ is 0.93×10 -6 K -1 .

[0064] Figure 5 The mechanical property curves of the C / SiC composite material prepared in Control Example 1, wherein a is the bending stress-strain curve, and b is the fracture toughness force-displacement curve.

[0065] After testing, the bending strength of the C / SiC composite material prepared in Control Example 1 is 338±8MPa, and the fracture toughness is 20.3±1.1MPa / m 2 .

[0066] Compared with Control Example 1, Example 1 introduces a silicon nitride matrix into the fiber bundle through a chemical vapor deposition process, so that the silicon nitride matrix completely wraps the fiber bundle, forming a large number of diffusely distributed microcracks in the fiber bundle, greatly alleviating the thermal mismatch between the fiber bundle and the matrix, and ultimately reducing the expansion coefficient to near zero. The silicon carbide matrix with a higher modulus is deposited on the outside of the fiber bundle, while limiting the microcracks within the fiber bundle, it also greatly maintains the mechanical properties, and the bending strength is only reduced from 338±8MPa in Control Example 1 to 329±5MPa in Example 1. Compared with a near-zero expansion carbon fiber reinforced multi-layer matrix composite material disclosed in the prior art, its preparation cycle is also reduced from 4-5 months to 2-3 months.

[0067] In summary, the composite material provided by the present invention includes a carbon fiber bundle, a pyrolytic carbon interface layer on the surface of the carbon fiber bundle, a silicon nitride matrix layer that completely wraps the carbon fiber bundle, and a silicon carbide matrix layer outside the carbon fiber bundle. The silicon nitride matrix layer that completely wraps the carbon fiber bundle is: only silicon nitride matrix exists between the fiber filaments inside the carbon fiber bundle, and silicon nitride matrix with a thickness of 0.5 to 5 μm exists between the fiber filaments at the edge of the carbon fiber bundle and the silicon carbide matrix; the present invention adjusts the deposition time of the silicon nitride matrix so that the silicon nitride matrix completely wraps the carbon fiber bundle, forming diffusely distributed microcracks in the fiber bundle, thereby achieving near-zero expansion.

[0068] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A near-zero expansion C / Si3N4-SiC composite material, characterized in that: The composite material comprises a carbon fiber reinforced silicon nitride-based porous composite material and a silicon carbide matrix coated on the surface of the carbon fiber reinforced silicon nitride-based porous composite material; The carbon fiber reinforced silicon nitride-based porous composite material comprises a carbon fiber preform woven from carbon fiber bundles; a pyrolytic carbon interface layer is deposited on the carbon fiber bundles in the carbon fiber preform, and the pyrolytic carbon interface layer is also coated with a silicon nitride matrix; The fiber monofilaments inside the carbon fiber bundle contain a silicon nitride matrix; the fiber monofilaments at the edge of the carbon fiber bundle and the silicon carbide matrix contain a silicon nitride matrix with a thickness of 0.5 to 5 μm.

2. The near-zero expansion C / Si3N4-SiC composite material according to claim 1, characterized in that: The thickness of the pyrolytic carbon interface layer is 100-500 nm; the thickness of the silicon carbide matrix layer outside the carbon fiber bundle is 0.02-0.3 mm.

3. The near-zero expansion C / Si3N4-SiC composite material according to claim 1, characterized in that: The diameter of the fiber monofilaments in the carbon fiber bundle is 4-8 μm; the number of the fiber monofilaments in the carbon fiber bundle is 1K, 3K, 6K or 12K; the carbon fibers in the carbon fiber bundle are T series fibers; The carbon fiber preform structure includes a 2D carbon fiber preform, a 2.5D carbon fiber preform or a 3D woven carbon fiber preform.

4. The near-zero expansion C / Si3N4-SiC composite material according to claim 1, characterized in that: The density of the composite material is 1.9-2.1 g / cm 3 The open porosity is 8~15vol.%; the absolute value of the thermal expansion coefficient of the composite material in the temperature range of -100~100℃ is less than 0.1×10 -6 K -1 .

5. A method for preparing the near-zero expansion C / Si3N4-SiC composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Weaving continuous carbon fiber bundles into carbon fiber preforms with different structures and a fiber volume fraction of ≥38%; The carbon fiber preform is placed in a vacuum furnace, the pressure is set to <300Pa, the temperature is 800-900°C, argon and propylene are introduced, and the temperature is kept for 45-200 hours, a pyrolytic carbon interface layer is deposited on the surface of the carbon fiber preform, and then a heat treatment is performed at 1200-1900°C for 1-2 hours; The carbon fiber preform after the pyrolytic carbon interface layer is deposited and heat treated is set to a pressure of less than 300 Pa and a temperature of 800-1100°C, and argon, hydrogen, silicon tetrachloride and ammonia are introduced, and the carbon fiber bundle is completely wrapped by the silicon nitride matrix by adjusting the deposition time to obtain a carbon fiber reinforced silicon nitride-based porous composite material; A carbon fiber reinforced silicon nitride-based porous composite material is placed in a deposition furnace, the pressure is set to <300Pa, the temperature is 1000~1100℃, argon, hydrogen and trichloromethylsilane are introduced, a silicon carbide matrix is ​​generated by reaction on the surface of the silicon nitride matrix, and the pores between the carbon fiber bundles are filled to obtain a near-zero expansion C / Si3N4-SiC composite material.

6. The method for preparing the near-zero expansion C / Si3N4-SiC composite material according to claim 5, characterized in that: When the pyrolytic carbon interface layer is deposited on the surface of the carbon fiber preform, the flow rate of the introduced argon gas is 2-4 L / min, and the flow rate of the introduced propylene is 2-4 L / min.

7. The method for preparing the near-zero expansion C / Si3N4-SiC composite material according to claim 5, characterized in that: When preparing the C / Si3N4 porous composite material, the flow rate of argon gas is 2~4L / min, the flow rate of hydrogen gas is 7~9L / min, the flow rate of silicon tetrachloride is 3~5L / min, and the flow rate of ammonia gas is 2~4L / min.

8. The method for preparing the near-zero expansion C / Si3N4-SiC composite material according to claim 5, characterized in that: When a silicon carbide substrate is generated by reaction on the surface of a silicon nitride substrate, the flow rate of the introduced argon gas is 2-4 L / min; the flow rate of the introduced hydrogen gas is 4-6 L / min; and the molar mass ratio of the hydrogen gas to trichloromethylsilane is 10:

1.

9. Use of the near-zero expansion C / Si3N4-SiC composite material according to any one of claims 1 to 4 in space optical-mechanical structural parts.

Citation Information

Patent Citations

  • C / SiC ceramic matrix composite material and preparation method thereof

    CN102690124A

  • Densification method for carbon fiber reinforced silicon carbonitride ceramic composite material

    CN103724035A

  • Preparation method of C / SiC structure material with near-zero expansion characteristic

    CN111217616A

  • High-temperature-resistant ceramic matrix composite interface composite coating and preparation method

    CN111517810A

  • Near-zero-expansion carbon fiber reinforced multi-element multi-layer matrix composite material as well as preparation method and application thereof

    CN117185818A